Innovative design and construction of a mini coin sorter device - Hayaroni, Ikhwan Hafiz; Mohd Yusof, Ab Aziz (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
A mini coin sorter machine is a device designed to sort coins into different categories. Often, coins are stored together without being sorted, leading to disorganization in daily life. This project aims to address this issue within our community. The project includes several objectives, such as designing a prototype and fabricating the machine. Additionally, the project explored the concept and mechanism of the mini coin sorter machine, the fabrication process, and how the machine operates. This involves considering the materials used for fabrication, determining the necessary components and engineering requirements. Furthermore, the project provide instructions for manual operation and safety precautions. Issues such as using low quality materials and limitations in workplace utilities may affect the final product, prompting recommendations for improvement. Through this discussion, the project aims to identify areas for enhancement and contribute to the development of more efficient mini coin sorter machines in the future.